Making the user useful? How translation processes managerialize voice in public organizations - Jacob Reilley; Nathalie Iloga Balep; Christian Huber (Financial Accountability & Management, 2020)
One of the most pervasive topics in public management discussions in recent decades is the notion of user orientation. More than ever, external stakeholders expect public organizations to “get closer” to users and to treat citizens as knowledgeable consumers of public services with a view and a voice. Existing literature highlights how, through a wide range of calculative practices, information gathered from and about public service users is assembled into descriptions of organizational activity that are useful for managers in addressing issues of surveillance and internal control as well as legitimation. In our multiple case study of hospitals and prisons in Germany, we introduce a two-step model of translation for explaining how user voice is transformed into management objects, which are then further translated into organizationally “useful” information. In doing so, we make three contributions to further our understanding of how user views are formatted to organizational activity and put to use by managers in the public sector. First, we developed a model of translation that highlights how user voices and the prospect of user orientation are enacted across diverse organizational contexts. Second, we found that different types of organizations deploy distinct methods of accounting, which nevertheless make user feedback useful in similar ways: to develop information that helps construct an image of performance, gain financial leverage, and enact compliance. Third, we found that in addition to quantitative forms of accounting, narrative accounting techniques played important roles in making users “useful” in public organizations.
Keywords: 650; accounting; management; translation; usefulness; user voice